A Study On Drug Use And Criminal Behaviours Of Criminal Offenders In The State Of Penang - Hadep Singh, Balber Singh (2023)
People who use drugs (PWUDs) tend to commit crime under the influence of drugs compare with people without drug use history. Though researchers have argued that drug use can cause people to engage in crime, however, the relationship between drug use and crime seems insufficiently investigated. This study aims to investigate the criminal profile of Police detainees who were caught under the Penal Code (Act 574) for various crime offenses between June and December 2019 in the Northeast and Southwest Districts of Penang State. A total of 73 Police detainees were recruited through convenience sampling for this cross-sectional study. Majority were males (93%, n=68/73), most Malays (58%, n=42/73), and the sample’s mean age in this study was 32.8 years (SD=8.13). About 16% (n=12/73) of the detainees had previous drug rehabilitation history, while 55% (n=40/73) had been incarcerated before. Fifty-six percent (n=41/73) of the detainees were detained for non-violent offenses (e.g., property crime), and 44% for violent offenses (e.g., gang robbery, physical assault, etc.) under the Penal Code (Act 574). Of this, 81% (n=59/73) of the offenses were categorised as bailable offenses. As for their drug use status, 62% (n=45/73) of the detainees tested positive for illicit drug use, most (53%) for amphetamine-type stimulant (ATS) and opiate (18%), when they were brought into detention. Sixty-eight percent (n=50/73) of the detainees had illicit drug use history. Most (59%, n=43/73) reported committing crime individually, and 41% usually committed crime with their acquaintances. About 8% held dangerous weapons while committing crime, and 41% (n=30/73) claimed that they were ordered by their superiors to commit crime.